Perancangan Aplikasi Penjualan Berbasis Web Pada Toko Gorden Aneka - Daniel Vebrianto; Jap Tji Beng; Desi Arisandi (CV. ITTC INDONESIA, 2025)
The advancement of information technology and the internet has significantly transformed consumer behavior and sales systems. Toko Gorden Aneka, located in North Jakarta, still relies on conventional sales methods, which limits its market reach and causes inefficiencies in daily transaction management. This study aims to design and implement a web-based sales application to enhance operational efficiency and expand the store’s market coverage. The development methodology used is the Software Development Life Cycle (SDLC) with the Waterfall model, encompassing the stages of requirement analysis, system design, implementation, testing, and maintenance. Technologies employed in the application development include Node.js, React.js, TypeScript, MySQL, and Tailwind CSS. Testing results using the black-box method and the System Usability Scale (SUS) indicated that the system functioned properly and received an average usability score of 86.1, reflecting high user satisfaction. This system is expected to support the digital transformation of Toko Gorden Aneka and improve its competitiveness in the e-commerce industry..